In Silico Screening For The Identification And Characterization Of Potential Mutations That Confer To Antibiotic Resistance In Malaysian Mdr-Tb Isolates - Teh, Hui Wen (2023)
The emergence of multidrug resistance tuberculosis (MDR-TB) is caused by the adaptation of Mycobacterium tuberculosis to survive in the presence of antibiotic, which is also contributed by mutations in the MDR-associated genes. Previous studies showed that the knockdown of fhaA gene expression led to peptidoglycan (PG) precursors the accumulating at the bacillary septum and poles, this indicates a probable defect in PG biosynthesis. As a result, the cell wall becomes impermeable to antibiotic, causing MDR. In this study, bioinformatics analyses were performed on MDR-TB isolates from 24 clinical samples to search for novel mutations that contribute to antibiotic resistance. We found out a potential deletion of nucleotides encoding 6 amino acids in 13 samples, in fhaA gene (RV0020c). Subsequent structural analysis shows that the deletion is located at the locus position 243-248, located near the N-terminal of the FHAA protein. Since FHAA protein has a function by binding to MviN protein, it regulates cell growth and peptidoglycan synthesis, we postulated that the deletion will potentially cause the loss of its binding affinity to MviN, resulting in the inhibition and blockage of the peptidoglycan polymerization, causing MDR in MTB. Similarly, another 6 amino acid deletion was also detected for hbhA gene (Rv0475) in 12/14 drug resistant samples. HBHA protein has a function of inducing aggregation in mycobacterial.